INNV-20. RADIOGRAPHIC RESPONSE AND SEIZURE CONTROL IN IDH1 MUTANT GLIOMA PATIENTS USING IVOSIDENIB. (12th November 2021) - Peters, Katherine; Patel, Mallika; Alford, Candice; Chavez, Gerardo; Kim, Jung-Young; Durling, Jennifer; Novack, Tracy; Batich, Kristen; Shoaf, Madison; Hanzlik, Emily; Affronti, Mary; Johnson, Margaret; et al.
Abstract: Isocitrate dehydrogenase 1 (IDH1) is commonly mutated in grade II-III gliomas, and the mutant enzyme leads to the production of the oncometabolite 2-hydroxyglutarate (2-HG). 2-HG is responsible for the gliomagenesis associated with these tumors and the promotion of seizures via glutamate receptors. Ivosidenib, a small molecule oral mIDH1 inhibitor, has shown promise in clinical trials to treat IDH1 mutant gliomas, and providers can utilize this agent in IDH1 mutant glioma patients. We evaluated our IDH1 mutant glioma patients treated off-label with ivosidenib and described the radiographic response and seizure control in this cohort when ivosidenib was initiated between October 2020 to February 2021. Radiographic response was determined using RANO criteria, and seizure control was determined by comparing seizures per month before and after initiation of ivosidenib. All patients represented received single-agent ivosidenib dosed at 500 mg orally once a day. One patient required a dose reduction to 250 mg orally once a day because of drug-induced diarrhea. In our cohort of six patients, patient age range was 31 to 74 years with four female patients and two male patients. Diagnoses represented were astrocytoma, IDH1 mutant (n=3) oligodendroglioma (WHO), IDH1 mutant, 1p19q co-deleted (n=2), and anaplastic astrocytoma IDH1 mutant (n=1). Three patients experienced a reduction of seizure frequency, two patients did not have seizures before or after therapy, and one patient remained with the same level of seizures (1 seizure/month). Radiographic responses recorded included three patients with stable disease, two patients with minor responses, and one patient with a partial response. Treatment with ivosidenib is ongoing for this cohort of mIDH1 glioma patients. Updated information on prolonged disease control and seizure control in this cohort of IDH1 mutant glioma patients will be presented. Therapeutics, such as ivosidenib, can lead to improved seizure control and radiographic outcomes in IDH1 mutant glioma patients.